Determinant factors of physical performance in rugby specific playing positions - Zabaloy, S.; Blanco, F. P.; Carlos-Vivas, J.; González, J. G. (Science & Sports, 2021)
Introduction: This study aimed to analyse the differences in force-velocity profile and sprint, strength and jump performance according to playing position, and to examine the relationships between these fitness parameters within rugby specific playing positions. Methods: Fifty-one male rugby players (27 backs, 24 forwards) were assessed in their force-velocity profile, vertical jumps, 5 and 30 m sprint, and strength in squat and bench press exercises. For a deeper understanding of positional differences, forwards were divided into front row and back five, and backs were split into outside and inside backs. Results: Forwards showed higher body mass and height, greater sprint momentum and higher absolute strength than backs, whereas backs were faster in 5 and 30 m sprints. No significant differences were observed between outside and inside backs for any of the variables analysed. Front row forwards were significantly heavier than back five, whereas the latter showed higher jump and sprint performance and greater maximum power values than front row. No significant differences were observed between any positions for force-velocity imbalance. No correlations were found between force-velocity imbalance and any physical performance variable regardless of playing position. Maximum power (r = 0.434 to 0.855; P < 0.05) and relative strength (r = 0.404 to 0.772; P < 0.05) were the variables that most correlate with jump and sprint performance in forwards and backs. Conclusion: Clear differences exist between backs and forwards in strength and sprint performance. Although no differences were observed between specific backs positions, in contrast to the specific forwards positions that showed clear differences in all the physical performance variables. High levels of relative strength and power may be relevant in order to attain high sprinting and jumping performance.